HUBUNGAN KARAKTER PSIKOLOGIS DAN MOTIVASI BERPRESTASI DENGAN PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (Studi Empirik Kuantitatif pada Peserta Didik Paket B PKBM Mandiri An-Nuur Depok Jawa Barat) - Saeful Bahri (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2021)
In general, this study aims to determine the relationship between psychological character and achievement motivation with student achievement in learning achievement of students in Islamic Religious Education subjects, either partially / individually or simultaneously/ collectively. This study used a survey method with data collection tools using questionnaires and tests. Meanwhile, data analysis used descriptive analysis to see the distribution of samples, statistical analysis prerequisite tests, simple and multiple partial correlation and simple and multiple regression tests. The sample in this study students of Package B (PKBM) Mandiri An-Nuur Depok City, West Java, totaling 93 students. The results of this study indicate that: First, there is a positive and significant relationship between psychological character and student achievement in the Islamic Religious Education subject. The simple correlation coefficient of Pearson correlation (ρy1) is 0.737 (strong correlation), and the significance value is 0.000 <0.05, with a large contribution of psychological character. toward student achievement in the subject of Islamic Religious Education (Y) of 54.4% and the direction of the relationship shows a simple linear regression equation, namely Ŷ = 42.871 + 0.356 X1 which means that every one unit increase in psychological character scores will contribute to an increase in student achievement scores. Islamic Religious Education lessons of 43.227. Second, there is a positive and significant relationship between student achievement motivation and student achievement in the PAI subject with the simple correlation coefficient of the Pearson correlation (ρy2) is 0.702 (strong correlation), and the significance value is 0.000 <0.05, with the contribution of achievement motivation to the Student achievement in the subject of Islamic Religious Education (Y) is 49.3% and the direction of the relationship shows a simple linear regression equation, namely Ŷ = 45.458 + 0.333 X2, which means that each unit increase in achievement motivation scores will contribute to an increase in student achievement scores in the Islamic Religious Education lessons of 45.79. Third, there is a positive and strong and significant relationship between psychological character (X1) and achievement motivation (X2) together with student achievement in the subject of Islamic Religious Education (Y), with a simple correlation coefficient Pearson correlation (Ry1.2) is 0.756 (strong correlation), and the significance value is 0.000 <0.05, with the magnitude of the contribution of psychological character and achievement motivation together to student achievement in the subject of Islamic Religious Education (Y) of 57.2% and the direction of the relationship shows a linear regression equation double, namely Ŷ = 39.967 + 0.239X1 + 0.140X2, which means that every one unit increase in psychological character score and achievement motivation together, will contribute to an increase in student achievement scores in the Islamic Religious Education subject by 40.346